Hepatitis E virus in patients with decompensated chronic liver disease: a prospective UK/French study. Issue 5 (14th July 2015) - Blasco‐Perrin, H.; Madden, R. G.; Stanley, A.; Crossan, C.; Hunter, J. G.; Vine, L.; Lane, K.; Devooght‐Johnson, N.; Mclaughlin, C.; Petrik, J.; Stableforth, B.; Hussaini, H.; et al.
Summary Background In developed countries, hepatitis E is a porcine zoonosis caused by hepatitis E virus (HEV) genotype 3. In developing countries, hepatitis E is mainly caused by genotype 1, and causes increased mortality in patients with pre‐existing chronic liver disease (CLD). Aim To determine the role of HEV in patients with decompensated CLD. Methods Prospective HEV testing of 343 patients with decompensated CLD at three UK centres and Toulouse France, with follow‐up for 6 months or death. IgG seroprevalence was compared with 911 controls. Results 11/343 patients (3.2%) had acute hepatitis E infection, and three died. There were no differences in mortality (27% vs. 26%, OR 1.1, 95% CI 0.28–4.1), age (P = 0.9), bilirubin (P = 0.5), alanine aminotransferase (P = 0.06) albumin (P = 0.5) or international normalised ratio (P = 0.6) in patients with and without hepatitis E infection. Five cases were polymerase chain reaction (PCR) positive (genotype 3). Hepatitis E was more common in Toulouse (7.9%) compared to the UK cohort (1.2%, P = 0.003). HEV IgG seroprevalence was higher in Toulouse (OR 17, 95% CI 9.2–30) and Truro (OR 2.5, 95% CI 1.4–4.6) than in Glasgow, but lower in cases, compared to controls (OR 0.59, 95% CI 0.41–0.86). Conclusions Hepatitis E occurs in a minority of patients with decompensated chronic liver disease. The mortality is no different to the mortality in patients without hepatitis E infection. The diagnosis can only be established by a combination of serology and PCR, the yield and utility of which vary by geographical location.